How villagers in central Sierra Leone understand infection risks under threat of Covid-19. - Foday Mamoud Kamara; Esther Yei Mokuwa; Paul Richards (PLoS ONE)
Background Concern has been expressed over how well Africa is prepared to cope with the pandemic of Covid-19. Will rural populations with low levels of education know how to apply community-based infection control? We undertook fieldwork in two villages in central Sierra Leone to gain insight into how rural people faced with Covid-19 assess epidemic infection risks. Methods Two communities were selected based on prior contrasted exposure to Ebola Virus Disease-one with substantial number of cases and the other having resisted infection through strong community sequestration measures. We assessed understanding of infection risks via an experimental game. This asked players to express a preference for one of two diseases, one resembling Ebola with lower risk of infection and the other resembling Covid-19 with lower risk of death. Players were not told the identity of the diseases. Results In total 107 adult villagers played the game (58% women). Half (52%) preferred the disease model with lower risk of infection, 29% preferred the model with lower risk of death, while 21% saw the combined risk of infection and death as being equivalent. Differences in reactions between the two locations were small despite different experiences of Ebola. Asked to explain their choices 48% of players cited information on infection risks modelled by the game and 31% stated that their choices reflected awareness of the need for personal action and respect for local regulations. We concluded that villagers thoughtfully assess disease risks and that some are good intuitive statisticians. Conclusions Results suggest rural people in Sierra Leone retain the lessons of experience from the Ebola outbreak of 2014-15 and will be able to apply these lessons to a new infectious disease for which have no prior practical experience. Our expectation is that rural populations will understand Covid-19 control measures, thus reducing need for draconian enforcement.